ANALISIS KEY SUCCESS FACTORS SEBAGAI ALAT MEMPERTAHANKAN KEUNGGULAN BERSAING - Kumala Sari, Henny Puspita; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out the identification and the analysis of Key Success Factor in achieving competitive benefit at clothing store Cosmic Surabaya branch. The method of the research has been done by using qualitative method. It is carried out by using descriptive analysis. The strengths factor include sale promotion, brand expansion and innovation, and from the existing strength by expanding outlets in some big cities in Indonesia and by making musical events, meet and greet skateboard community, longboard, and fingerboard. The weaknesses factor include characteristic of less variation products, delivery process depends on shipping company which has cooperated with the company. The opportunities factor which includes: (1) the innovation of the company with the presence of fashion development for the people who wear veils; (2) by making expansion of market segmentation, take the available market share, conduct cooperation with other companies; Threats factor which include the occurrence of new competitors in field of clothing store and price competition. companies can find out their weaknesses, strengths, opportunities and threats so companies can improve their competitive benefit and they can measure their performance. Therefore, companies need to maintain their relationship to the customers, their service quality, and conduct business diversification.Keywords: Critical Success Factors, SWOT Analysis, Competitive Benefits